Scaling Laws of Bottle‐Brush Polymers in Dilute Solutions. Issue 6 (3rd November 2016) - Chatterjee, Debarati; Vilgis, Thomas A.
Abstract : Using molecular dynamics (MD) simulations, this study shows that the persistence length (which is a rigidity marker of any polymeric backbone) tends to merge to a strong dependence on the number of monomers of the long side‐chains for a bottle‐brush polymer. Thus, the rigidity dependence and related structural variations with the sidechains of bottle‐brush polymers are elucidated here. Abstract : The structural determination and manipulation of bottle‐brush polymers, a class of polymers with serially grafted side‐chains, is challenging due to the interplay of side‐chain and backbone interactions over various length scales. The present work performs a detailed analysis, using molecular dynamics simulation techniques, to unravel these interactions by probing the distinct rod to a flexible real‐chain with self‐avoiding walk (SAW) type crossover in the backbone static structure factor. This analysis elucidates the deviation from flexible chain behavior, while also providing a quantitative measure of persistence length, l P . Significantly, the results identify a trend in l P which is consistent with the debated theoretical prediction of l P ∼ N s 15 / 8, where N s is the number of monomers in each side‐chain of the bottle‐brush polymer.